The Use of Adipose-Derived Progenitor Cells and Platelet-Rich Plasma Combination for the Treatment of Supraspinatus Tendinopathy in 55 Dogs: A Retrospective Study - Canapp, Sherman O.; Canapp, Debra A.; Ibrahim, Victor; Carr, Brittany Jean; Cox, Catherine; Barrett, Jennifer G. (Frontiers in Veterinary Science, 2016)
Objective: To report clinical findings and outcomes for 55 dogs with supraspinatus tendinopathy treated with adipose derived progenitor cells and platelet rich plasma therapy. Methods: Medical records of client-owned dogs diagnosed with supraspinatus tendinopathy that were treated with adipose derived progenitor cells and platelet rich plasma (ADPC-PRP) combination therapy were reviewed from 2006-2013. Data collected included signalment, medical history, limb involvement, prior treatments, physical and orthopedic examination, objective temporospatial gait analysis findings, diagnostic imaging results (radiography, magnetic resonance imaging, musculoskeletal ultrasonography), arthroscopy findings, and outcome. Results: Following ultrasound-guided injection of ADPC-PRP, objective gait analysis was available on 25 of the 55 dogs at 90 days post ADPC-PRP therapy. Following treatment, a significant increase in total pressure index percentage (TPI%) was noted in the injured (treated) forelimb at 90 days post treatment (p = 0.036). At 90 days following treatment, 88% of cases had no significant difference in TPI% of the injured limb to the contralateral limb. The remaining 12% of cases had significantly improved (p=0.036). Bilateral shoulder diagnostic musculoskeletal ultrasound revealed a significant reduction in tendon size (CSA) in the treated tendon at 90 days following treatment when compared to the initial CSA (p=0.005). All cases showed significant improvement in fiber pattern of the affected supraspinatus tendon by the ultrasound shoulder pathology rating scale. Clinical Relevance: These findings suggest that ADPC-PRP therapy should be considered for dogs with supraspinatus tendinopathy. Abbreviations: ST: supraspinatus tendinopathy ADPC: adipose derived progenitor cells MSC: mesenchymal stem cells PRP: platelet rich plasma TPI%: total pressure index percentage